Correlation of mutations with the minimum inhibitory concentrations of isoniazid drug among isoniazid-resistant Mycobacterium tuberculosis isolates in Bangladesh - Ruhee, Noshin Nawer (Brac University, 2024)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.